Escherichia coli O157:H7 Bacteria Antibiotic Resistant Isolated from Flies at Food Courts in IPB Dramaga Campus - Aminudin, Muhammad Rizki; Lukman, Denny Widaya; Sudarwanto, Mirnawati Bachrum; Pisestyani, Herwin (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2024)
Several human and animal pathogens transmit into the food chain through houseflies as mechanical vectors, one of which is E. coli O157:H7. E. coli O157:H7 can express Shiga toxin (Stx) which can cause diarrhea, hemorrhagic colitis, and potentially fatal hemolytic-uremic syndrome (HUS) in humans. Some pathogen strains show resistance against various antibiotics, causing complex health problems. This study aims to analyze the presence of antibiotic-resistant E. coli O157:H7 bacteria carried by houseflies (M. domestica) in the food court IPB Dramaga campus area. Detection of E. coli O157:H7 on fly legs using qPCR method based on MU 7.2.3.32-8. E. coli O157:H7 isolates were tested for sensitivity to the antibiotic’s ciprofloxacin, ampicillin, tetracycline, trimethoprim-sulfamethoxazole, cefepime, chloramphenicol, ceftazidime, cefotaxime, and ceftriaxone using the Kirby Bauer disc diffusion method. This study isolated 5 E. coli isolates (5/40; 12.5%), and 2 of them were confirmed as E. coli O157:H7. One isolate of E. coli O157:H7 was resistant against ampicillin and tetracycline, and one isolate was resistant against ampicillin, tetracycline, trimethoprim-sulfamethoxazole, and ceftazidime. The multi-drug resistance was identified only in 1 isolate of E. coli O157:H7.Houseflies collected from the food court have the potential to transmit antibiotic-resistant E. coli O157:H7 around the IPB campus.